Portal venous gas resulting from umbilical vein catheterization in a very‐low‐birth‐weight infant with no interruption in early feeding - Jun Wang; Guang Yue; Hua Yang; Jing Li; Rong Ju (Wiley, 2021)
ABSTRACT Introduction Portal venous gas (PVG) is common in necrotizing enterocolitis and occasionally occurs in neonates after umbilical vein catheterization (UVC). Therefore, determining the cause of PVG requires further clinical evaluation in these cases. Case presentation We report the case of a very‐low‐birth‐weight infant who underwent UVC after birth. PVG was an unexpected finding on ultrasound following catheterization. The UVC was immediately removed and replaced with a peripherally inserted central catheter. The infant's physical examination was unremarkable. Bedside X‐ray revealed neither PVG nor pneumatosis intestinalis, which would indicate the onset of necrotizing enterocolitis. After full evaluation, breastfeeding was started on the same day. The infant did not develop feeding intolerance, necrotizing enterocolitis, or other disorders. Conclusion PVG occasionally occurs in neonates who undergo UVC and is considered to be caused by exogenous gases. PVG is more easily detected with ultrasound than with X‐ray and does not affect early feeding in premature infants.